Teachers’ Perspectives on the Application of Teaching Methods in Group Electone Instruction - Yang, Chan (Pacific International Journal, 2025)
This study explores teachers’ perspectives on the application of teaching methods in group Electone instruction, with a focus on how instructional strategies influence student engagement, peer collaboration, and ensemble performance skills. Two participating teachers—one leading a kindergarten group of four students and another guiding a mixed-level group of four—were observed over five complete lessons each. Data were collected through structured lesson observations, post-lesson semi-structured interviews, and supplementary materials including photographs, annotated scores, and rehearsal notes. Thematic analysis revealed distinct pedagogical priorities: one teacher emphasized cooperative ensemble playing, structured repetition, and confidence-building in young beginners, while the other focused on technical precision, interpretive detail, and independent preparation among mixed-level learners. Across both cases, challenges were noted in balancing individual and group needs, sustaining attention, and ensuring consistent home practice. Comparative analysis highlighted differences in instructional pacing, feedback styles, and the integration of creative elements such as storytelling and visual aids. These findings offer practical insights for Electone educators seeking to optimize group lesson dynamics and suggest that effective group instruction requires adaptive strategies that align with student developmental stages, technical abilities, and ensemble goals.